Numerical investigation of critical electrochemical factors for pitting corrosion using a multi-species reactive transport model. (February 2021) - Sun, Xiangming; Srinivasan, Jayendran; Kelly, Robert G.; Duddu, Ravindra
Abstract: A multi-species reactive transport model based on the sequential non-iterative approach is employed to investigate two major stages involved in artificial pit experiments of stainless steel: I. Stable dissolution under a salt film and II. Film-free dissolution that transitions to repassivation. Data of current density and electrical potential obtained from rapid polarization scans of pits with different depths are utilized to calibrate the elapsed time and the electrode kinetics of each stage. The local chemistry near the base of pits at different temperature and bulk concentrations is simulated to determine several critical electrochemical factors at saturation and repassivation.